2019
DOI: 10.1158/0008-5472.can-18-1805
|View full text |Cite
|
Sign up to set email alerts
|

A Blazing Landscape: Neuroinflammation Shapes Brain Metastasis

Abstract: Brain metastases are more common than primary CNS tumors, and confer grave prognosis on patients, as existing treatments have very limited efficacy. The tumor microenvironment has a central role in facilitating tumorigenesis and metastasis. In recent years, there has been much progress in our understanding of the functional role of the brain metastatic microenvironment. In this review we discuss the latest advances in brain metastasis research, with special emphasis on the role of the brain microenvironment an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
53
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(57 citation statements)
references
References 171 publications
(171 reference statements)
3
53
0
1
Order By: Relevance
“…Although the use of immune checkpoint inhibitors targeting PD-1 and/or CTLA-4 has nowadays become an established therapy in melanoma, it is still critical to transfer our knowledge from extracranial sites to intracranial melanoma lesions with respect to the unique "immune-specialized" microenvironment of the brain (54,55). After extravasation of tumor cells into the brain parenchyma they enter a fundamentally different tissue environment with respect to the metabolic situation, the cellular compositions, the brain-specific extracellular matrix proteins and the immunoreactive heterogenous cell population with regard to the primary site of their origin (56).…”
Section: Discussionmentioning
confidence: 99%
“…Although the use of immune checkpoint inhibitors targeting PD-1 and/or CTLA-4 has nowadays become an established therapy in melanoma, it is still critical to transfer our knowledge from extracranial sites to intracranial melanoma lesions with respect to the unique "immune-specialized" microenvironment of the brain (54,55). After extravasation of tumor cells into the brain parenchyma they enter a fundamentally different tissue environment with respect to the metabolic situation, the cellular compositions, the brain-specific extracellular matrix proteins and the immunoreactive heterogenous cell population with regard to the primary site of their origin (56).…”
Section: Discussionmentioning
confidence: 99%
“…While the specific nature of NfL liberation after neuronal damage is unknown, elevations have been observed in a variety of mechanisms from trauma [ 9 , 13 ], degenerative processes [ 7 , 10 , 14 ], ischemia/anoxia [ 11 , 15 ], human immunodeficiency viruses-infections [ 16 ] and hematoma compression [ 17 ]. Hence, a release of NfL would be expected as a consequence of the neuronal damage caused by the infiltration of the brain metastasis in the brain parenchyma [ 18 ] and/or brain compression caused by the metastasis. In line with this, a recent study found elevated NfL levels in seven cancer patients with brain metastasis compared with healthy controls [ 19 ], which supports our findings.…”
Section: Discussionmentioning
confidence: 99%
“…Brain metastases are recognized as “one of the deadliest forms of tumor metastasis” [ 159 ], occurring most commonly in advanced malignancies that are associated with an intense systemic inflammatory response. These include breast and lung cancers, as well as melanoma [ 159 , 160 , 161 , 162 ].…”
Section: Hmgb1 and Tumorigenesismentioning
confidence: 99%